The effect of live selling on purchase intention in students at telkom institute of technology Purwokerto - Suryaningtiyas, Y. D.; Rosiana, Monica; Marsally, Silvia Van (Jurnal Ekonomi, 2024)
Internet used for most Indonesians has become a lifestyle. Many young generations often carry out buying and selling transaction via e-commerce at social media, which is turns changes people’s shopping lifestyles. This was reinforced during the COVID-19 pandemic, more people’s using E-Commers and creating direct sales features that could increase people’s desire to buy goods. This research aims to analyse the influence of Live Selling, namely live broadcasts that allow sellers and buyers to interact directly. Where seller make sales by displaying the products offered to buyers buy products during live selling, namely interactivity, visualization, Entertainment and Professionalization. This research used quantitative research with random sampling techniques and 116 respondents were successfully collected for measurement. Data processing gives the following result (1) interactivity variable has a positive effect on purchase intention (2) Visualization variable has a positive effect on purchase intention (3) entertainment variable has a positive effect on purchase intention, (4) professionalization variable has a positive impact on purchase interest. Live Selling that fulfils these four components can increase purchasing intentions among students in ITTP.